Enhancing teaching methods for Islamic education teachers in primary schools - Ismail, Halim; Abdul Halim, Muhammad Syahir; Md Sidek, Suzana Suhailawaty (RMP Publications, 2023)
This study examines the methods implemented by Islamic Education Teachers (IET) in Kinta Perak's Northern District of Malaysia on teaching Ibadah (worship). This study also looks for differences in Ibadah teaching approaches based on gender and teaching experience. This study employs a survey method along with a quantitative approach. This study used a questionnaire to determine the ibadah teaching methodology. For this study, 100 sample IETs were chosen as the respondents. The data were analysed using descriptive statistics, independent samples t-tests, and one-way ANOVA. The study provides a mean score of 4.70 and a standard deviation of 0.34 for the whole data about the teachers' method of teaching ibadah, and the interpretation is high. The highest item in this construct item is “Reprimand pupils for their inaccurate prayer behavior,” with a mean of 4.86 (S.D. = 0.37). The independent sample t-test shows no significant differences in teachers’ methods in teaching ibadah based on gender. One-way ANOVA test shows no significant difference in teachers' methods in teaching Ibadah based on teaching experiences. As a result, ongoing efforts must be made to enhance teachers' abilities and student Ibadah practice. This study significantly strengthens the ibadah-related teaching strategies used by teachers.